Identification of Cytoprotective Small-Molecule Inducers of Heme-Oxygenase-1 - Gelare Ghajar-Rahimi; Amie M. Traylor; Bini Mathew; James R. Bostwick; N Miranda Nebane; Anna A. Zmijewska; Stephanie K. Esman; Saakshi Thukral; Ling Zhai; Vijaya Sambandam; Rita M. Cowell; Mark J. Suto; et al. (Antioxidants, 2022)
Acute kidney injury (AKI) is a major public health concern with significant morbidity and mortality and no current treatments beyond supportive care and dialysis. Preclinical studies have suggested that heme-oxygenase-1 (HO-1), an enzyme that catalyzes the breakdown of heme, has promise as a potential therapeutic target for AKI. Clinical trials involving HO-1 products (biliverdin, carbon monoxide, and iron), however, have not progressed beyond the Phase ½ level. We identified small-molecule inducers of HO-1 that enable us to exploit the full therapeutic potential of HO-1, the combination of its products, and yet-undefined effects of the enzyme system. Through cell-based, high-throughput screens for induction of HO-1 driven by the human HO-1 promoter/enhancer, we identified two novel small molecules and broxaldine (an FDA-approved drug) for further consideration as candidate compounds exhibiting an Emax ≥70% of 5 µM hemin and EC50 <10 µM. RNA sequencing identified shared binding motifs to NRF2, a transcription factor known to regulate antioxidant genes, including HMOX1. In vitro, the cytoprotective function of the candidates was assessed against cisplatin-induced cytotoxicity and apoptosis. In vivo, delivery of a candidate compound induced HO-1 expression in the kidneys of mice. This study serves as the basis for further development of small-molecule HO-1 inducers as preventative or therapeutic interventions for a variety of pathologies, including AKI.